Efforts to Protect the Legal Rights of Suspects of Abortion - Rizky Cahyo HD. Vinors (Estudiante Law Journal, 2019)
This study aims to find out how the Protection of The Rights of Suspects of Abortion Crimes in the City of Gorontalo and to find out what are the factors inhibiting the protection of the rights of suspected abortion crimes in the city of Gorontalo. This study is empirical research which in other words is field research, which is to review the provisions of applicable law and what happens in the community. The results of this study confirm that abortion is a strictly prohibited act by article 75 paragraph (1) of Law No. 36 of 2009 on health. In addition, this study refers to the protection of the rights of suspected abortion crimes, which is the concept where the law can provide justice, order, certainty, expediency, and peace. However, in this case, the suspect did not get his rights as stipulated in Article 50 of the Kitab Undang-Undang Hukum Acara Pidana, and contrary to Article 110 of the Kitab Undang-Undang Hukum Acara Pidana that the process of handling cases has a provision of days in the investigation process. The evidence that this case has stagnated for almost 1 (one) year and until now did not get clear legal certainty. In addition, the suspect did not make any effort because maybe the suspect did not know that he had the right to make legal efforts by the provisions of the law. Then in this case researchers found a factor that dominates the obstruction of the protection of the rights of suspected abortion crimes in the city of Gorontalo, namely the lack of understanding of the provisions of the day in the investigation, and the suspect who does not know his rights in the process of resolving abortion cases, he just waits for action from law enforcement officials so that in the end the case stagnates for 1 (one) year.